Advanced Mechatronics and MEMS Devices - Zhang, Dan (Microsystems, 2013)
Advanced Mechatronics and MEMS Devicesdescribes state-of-the-art MEMS devices and introduces the latest technology in electrical and mechanical microsystems. The evolution of design in microfabrication, as well as emerging issues in nanomaterials, micromachining, micromanufacturing and microassembly are all discussed at length in this volume. Advanced Mechatronics also provides a reader with knowledge of MEMS sensors array, MEMS multidimensional accelerometer, artificial skin with imbedded tactile components, as well as other topics in MEMS sensors and transducers. The book also presents a number of topics in advanced robotics and an abundance of applications of MEMS in robotics, like reconfigurable modular snake robots, magnetic MEMS robots for drug delivery and flying robots with adjustable wings, to name a few. This book also: Covers the fundamentals of advanced mechatronics and MEMS devices while also presenting new state-of-the-art methodology and technology used in the application of these devices Presents numerous applications of MEMS technology in robotics, using novel applications of micro-robots based on MEMS design and implementation Uses an extensive number of case studies Advanced Mechatronics and MEMS Devices is an ideal book for engineers,researchers, and graduate students who are interested in mechatronics and MEMS technology.